Conservation of Tropical Rainforests A Review of Financial and Strategic Solutions - McFarland, Brian Joseph (Palgrave Studies in Environmental Policy and Regulation, 2018)
This book critically engages with how the conservation of tropical rainforests is financed. Beginning with the context of tropical deforestation, alongside an overview of tropical ecology, global environmental policy and finance, the book reviews several conservation financing instruments. These include ecotourism and private reserves, debt-for-nature swaps and government domestic budgetary expenditures for state and national parks. Tropical deforestation and forest degradation are serious global environmental issues, contributing to global climate change, species extinction, and threatening the livelihoods of forest-dependent communities. Yet, many leading companies, individuals and governments are making a positive impact on tropical forest conservation to mitigate greenhouse gas emissions through the use of conservation finance. Conservation of Tropical Rainforests tells the history of international conservation finance and provides a variety of options for individuals, businesses, and governments to support conservation financing projects.